2018
DOI: 10.1002/chem.201801862
|View full text |Cite
|
Sign up to set email alerts
|

Latent and Air‐Stable Pre‐Catalysts for the Polymerization of Dicyclopentadiene: From Penta‐ to Hexacoordination in Molybdenum Imido Alkylidene N‐Heterocyclic Carbene Complexes

Abstract: The pentacoordinated, 16-valence electron (VE) Mo imido alkylidene N-heterocyclic carbene (NHC) complexes I1-I5 and the hexacoordinated 18-VE Mo imido alkylidene NHC complexes 1-4, 8, 10 and 12 containing a chelating ligand have been prepared and used as thermally latent catalysts in the ring-opening metathesis polymerization (ROMP) of dicyclopentadiene (DCPD). Both 10 and 12 are the first Mo imido alkylidene complexes with a chelating alkylidene featuring a carboxylate group. Complexes I1-I3 and I5 as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 28 publications
(81 citation statements)
references
References 56 publications
5
76
0
Order By: Relevance
“…Catalysts containing the more basic alkyl‐substituted imido ligands ( 8 , 11 , 17 a ) displayed decreased reactivity compared to complexes with aromatic imido ligands. This was also observed earlier . To demonstrate that this is a reactivity issue, we mixed catalyst 11 with 10 equiv 10‐undecenoic acid and monitored the reaction by 1 H NMR (Figure S122).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Catalysts containing the more basic alkyl‐substituted imido ligands ( 8 , 11 , 17 a ) displayed decreased reactivity compared to complexes with aromatic imido ligands. This was also observed earlier . To demonstrate that this is a reactivity issue, we mixed catalyst 11 with 10 equiv 10‐undecenoic acid and monitored the reaction by 1 H NMR (Figure S122).…”
Section: Resultssupporting
confidence: 75%
“…Until now, monocarboxylate species of Schrock‐type catalysts have not been reported. However, the monotriflate‐monocarboxylate species Mo( N ‐ t Bu)(CHCMe 2 Ph)(IMes)(O 2 CC 6 F 5 )(OTf) 10 can readily be prepared from 9 a (Scheme ). Subsequent transformation into the cationic monocarboxylate species 11 is facile and high‐yielding employing NaB(Ar F ) 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have shown that tailored six‐coordinate neutral Mo‐imido alkylidene NHC catalysts can serve as latent pre‐catalysts in the polymerization of dicyclopentadiene (DCPD) and are stable to air for at least 12 h . Here, we tested the air stability of our cationic complexes for a minimum of 12 hours.…”
Section: Resultsmentioning
confidence: 98%
“… Synthesis of cationic monocarboxylate species 11 – 15 from bistriflates 9 a – d via mixed monotriflate/monocarboxylate complex 10 or in situ generation of cationic monotriflate species and subsequent salt metathesis. Synthesis of cationic monocarboxylate complexes 17 a , b from dichloride NHC alkylidenes 16 a , b .…”
Section: Resultsmentioning
confidence: 99%
“…Such setup avoids any fast pre‐mixing of the components and thus simplifies the production process of poly‐DCPD, which is usually accomplished via reaction injection molding (RIM) or, in the case of fiber‐reinforced structures, via vacuum‐assisted resin‐transfer molding (RTM). Very recently, this concept has been extended to hexacoordinated 18‐VE complexes containing chelating NHCs and alkylidenes, respectively (Figure ) …”
Section: Molybdenum Imido Alkylidene Nhc Complexesmentioning
confidence: 99%